(3GdJQhjLs - (3ajdjH(B, (3chJdQs; (3Lhf ShfOQR(B, (3hCNQhfs ((3OeTb(B:s (3efThQGJ OGQ YdGA GdOjf(B,s, 2006)
(3ESJQGJjLjI GdGJUGdGJ GdJShjbjI GdeJcGedI,GdGJUGdGJ GdYGeI,GdOYGjI,JTLjY GdJQhjL hGdYdGbGJ eY GdQGj GdYGe,GdeHjYGJ GdTNUjI hEOGQI GdJQhjL,COGQI bfhGJ GdJhRjYs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdOYGjIs